Impact of climate change on livestock and agricultural production in Nepal (Triyuga Academic Journal, 2025)
This study finds out the perception of local Nepali community particularly of mountainous region of Gorkha district on adjustment of bad impact of climate change. The central point of research is about the control of livestock in the context of shifting of grass and supply of water. The research comprises of mixed-methods combining quantitative and qualitative data in Gorkhas Harmi Bhanjyang to know the effect of climate change on livestock supervision. Different methods such as household censuses, key informant interviews, focus groups discussion and observation of participants were used to gather information from local community, as well as cultivators and herders. Due to the changing climatic condition the study has shown that in present scenario, Harmi-Bhanjyang water sources are depleting in devastating manner which directly or indirectly affect farming practices as well as fauna. Conventional sources of water like ponds and streams have declined in such a way that springs are becoming less and the rate of flow of water is worst eventually leading to natural hazards such as droughts and landslides. Now the people of rural areas are migrating from the areas of uncertain climate to the region of stable climate due to the various reasons. Among them, the shortage of water for animals and for irrigation in farming practices contributes the more. Due to the changing climatic condition, huge number of livestock have been affected due to lack of rice straw, grazing land, and fodder especially for buffalo and cow. In analyzing the effect of climate change in case of adaptation and putting local people in trouble, increasing temperature and changing weather patterns have played tremendous role in distressing traditional agriculture practices. Particularly this study focuses on the serious effect of climate change on farming practices and in the case of animals in community of Harmi. Inhabitants of this community may not know about the effect of climate change but they feel various aspects such as huge difference in temperature, effect of precipitation either very low amount or very high and patterns of seasons. People who adapt to very low area of farming and have very low population of livestock suffer many difficultis and the study focuses on the importance of engaging traditional knowledge of local community into plan of adaptation. It searches for harmony and good focus to help for rural community and make rural people aware about the effect of change of climate.